RETRACTED (Expression of Concern/EoC): Pertanggungjawaban Direksi Secara Tanggung Renteng atas Pelanggaran Administratif di Bidang Pasar Modal - Sandhi Bagus Permana (Jurnal Hukum Lex Generalis, 2025)
Basically, there are no obstacles in processing this article in terms of substance, technical aspects, or administration. The editor states that the article authored by the writer, published in the Journal of Law Lex Generalis, is deemed worthy of publication. However, since the author in question objects to continuing the publication of the paper due to author safety reasons, which cannot be specified here, the Editorial Board, considering human rights, has decided to withdraw or carry out a retraction of this manuscript. The retraction referred to is related to an Expression of Concern (EoC), namely an external issue concerning the existence of an individual. We take this issue seriously, hence we have decided to take appropriate follow-up action. This statement is made for your understanding and for future evaluation. Thank you.